(untitled) (Al-Qalaa Journal, 2024)
Face detection concentrates on providing more security by using biological features and increasing security and privacy levels. In this paper, we proposed an approach to optimize the Haar-cascade algorithm developed from the OpenCV Computer vision library which was developed by Intel Company. The results revealed a clear enhancement and thereby improved the level of accuracy for the detected faces using Haar-Cascade